2017
DOI: 10.4236/jss.2017.58012
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Overview of Kohlberg’s Theory of Moral Development in College Moral Education in Mainland China

Abstract: Kohlberg's theory of moral cognitive development is temporarily the most influential theory in moral development psychology in the west and is still applied into practice and proved effective by moral theorists and educators all over the world. This paper takes this theory as the basis to analyze some problems existing in college moral education in China. It also suggests effective strategies to improve college moral education in China, i.e. Chinese colleges should reform the mode of moral education to increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 2 publications
0
5
0
2
Order By: Relevance
“…A person's level of morality can be measured by paying attention to the stages in his moral reasoning. Kohlberg identifies six levels of moral reasoning (Isaksson, 2014;Zhang, 2017), i.e., the preconventional level consists of stages 1 and 2, the conventional level consists of stages 3 and 4, and the post-conventional level consists of stages 5 and 6.…”
Section: Discussionmentioning
confidence: 99%
“…A person's level of morality can be measured by paying attention to the stages in his moral reasoning. Kohlberg identifies six levels of moral reasoning (Isaksson, 2014;Zhang, 2017), i.e., the preconventional level consists of stages 1 and 2, the conventional level consists of stages 3 and 4, and the post-conventional level consists of stages 5 and 6.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in mass parenting conditions, the results showed that children can learn moral through enforcing rules. Compliance with the rules for mass childcare in accordance with Kohlberg's theory of moral development [36], [37] at the pre-conventional stage, according to which the children's moral intelligence is related to social norms that result from the children's relationships with their environment. This moral enforcement only occurs when children are with other people [38].…”
Section: Discussionmentioning
confidence: 99%
“…Pengembangan kecerdasan moral pada anak usia dini akan memandu anak untuk memiliki interaksi sosial yang positif dan sehat (Bozaci, 2014); (Retnowati, Salim, & Saleh, 2018). Hal tersebut menunjukkan bahwa perkembangan moral seseorang sangat erat kaitannya dengan lingkungan sosialnya, sehingga Kohlberg menekankan bahwa pengembangan moralitas manusia dilakukan secara bertahap (Zhang & Zhao, 2017). Secara bertahap anak akan meningkatkan kecerdasan moralnya melalui model perilaku moral yang ditiru, serta memberikan penguatan dari lingkungan sosialnya (Ahyani & Dhini, 2011).…”
Section: Pendahuluanunclassified